Factors associated with overweight and obesity among adults 20.0 years and over results from the 2013 national nutrition survey, Philippines - Duante, Charmaine A.; Acuin, Cecilia Cristina S.; Austria, Rovea Ernazelle G.; Canag, Jay Lord Q.; Patalen, Chona F. (2019)
In 2016, the World Health Organization (WHO) estimated that at least 2.8 million people die each year as a result of overweight/ obesity associated with the occurrence of chronic diseases that has dire social and economic consequences. In the Philippines, the prevalence of overweight/ obesity among adults showed a gradually increasing trend. Local studies using national-scale data on the determinants of overweight/obesity among adults in the Philippines are found to be lacking as related studies available were done on selected population groups only. This study aimed to address this research gap and provide evidence for setting goals and targets to halt the increase of overweight/ obesity. Analysis of secondary data was done using the 2013 National Nutrition Survey results. Findings revealed that 30.0% of 9,076 adults 20.0 years and over with complete socio-demographic, socio-economic, anthropometric, clinical, and health and dietary data were overweight/ obese. Controlling for the effects of other variables, the factors significantly associated with overweight/ obesity among adults 20.0 years and over included adequacy of recommended energy intake, type of residence, age group, civil status, wealth quintile, highest educational attainment, and smoking status. The odds of being overweight/ obese was 29% higher among those who met the recommended energy intake compared to those who did not, and 28% higher among those living in urban areas than rural areas. As socio-economic status improved and as the population aged, the odds of overweight/ obesity increased. Adults with partners were more likely to be overweight/ obese than those who were single. In comparison to adults with no grade completed, the odds of being overweight/ obese were higher among those who were high school/vocational graduates and twice as high among college graduates. This study provides consistent evidence on the factors associated with overweight/ obesity, which may be addressed through multi-sectoral approach by crafting maximally effective programs and local policies. (Author's abstract)